The Provision of Genetic Testing and Related Services in Quebec, Canada - Unim, Brigid; De Vito, Corrado; Hagan, Julie; Villari, Paolo; Knoppers, Bartha Maria; Zawati, Ma’n (Frontiers in Genetics, 2020)
Background: Research in the field of genomics and genetics has evolved in recent years and so has the demand of consumers who are increasingly interested in genomic prediction of diseases and various traits. The aim of this study is to identify genetic service delivery models, policies governing the use of genomics medicine, and measures to evaluate genetic services in the province of Quebec, Canada. Methods: An ad hoc questionnaire was designed and administered online in 2017 to healthcare workers with good knowledge or experience in the provision of BRCA1/2, Lynch syndrome, familial hypercholesterolemia, inherited thrombophilia genetic tests, engaged in policy planning or evaluation of genetic services. A quali-quantitative analysis of the survey results was performed. Results: Thirty professionals participated in the study. The delivery models are classified in five categories according to the leading role of healthcare professionals in patient care pathways: "i) the geneticist model; ii) the primary care model; iii) the medical specialist model; iv) the population screening programme model; and v) the direct-to-consumer model". Barriers to genetic services are the coverage of genetic tests by the publicly funded healthcare system, the availability of qualified personnel, and the number of genetic centres. Regulatory oversight concerning the provision of genetic services appears to be insufficient. Conclusions: Integration between genetics and the overall healthcare system in Quebec is in an early phase. Current models of genetic services require good level of genetic knowledge by all medical specialists, collaboration among different healthcare personnel, and work redistribution. The proper implementation of genomics into healthcare can be achieved through education and training, proper regulatory oversight, genomic policies and public awareness.